Healthcare information system using cloud security - Shobana Pritha, P; A. Sasi Kumar, Dr (International Journal of Engineering and Technology, 2018)
Almost all the human living in Earth forgets to take care of their health. To say specifically, the elder ones and the younger ones need con-tinuous examination to note down the variation in their health issues (either improvement or a decrement). This can be achieved through the digitalization of the data. In the present day scenario information security and privacy in healthcare systems is an issue that is growing at alarming rate. The espousal of digital records of the patient, the enlarged order, provider integration and the growing need to exchange in-formation between patients, providers and payers each targets at the necessity for a developed information system. Inspite of so many measures taken to prevent the theft of patient's healthcare records offenders find some loophole or the other to get the records. This article strives to list certain health issues faced by a majority of people, threats to HIS, the method adopted to store huge amount of data and measures to prevent security threats.Â Â